Synergistic Effect of Glycyrrhizic Acid and ZnO/Palygorskite on Improving Chitosan-Based Films and Their Potential Application in Wound Healing - Qian Zhang (MDPI AG, 2021)
The synergistic effect of chitosan (CS), glycyrrhizic acid (GA) and ZnO/palygorskite (ZnO/PAL) as potential wound dressing was evaluated in the form of films by the solution casting method. The nanocomposite films were well-characterized with ATR-FTIR, XRD and SEM to explore the interactions between CS, GA and ZnO/PAL. Physical, mechanical and antibacterial properties of the nanocomposite films were systematically investigated for their reliability in end-up utilization. Importantly, it was found that the presence of PAL in the films provided enhanced mechanical properties, whereas CS, GA and ZnO supplied a broad-spectrum antibacterial activity, especially for drug-resistant bacteria such as ESBL—E. coli and MRSA. Overall, this research demonstrated that the prepared films can be a promising candidate for wound-care materials.